Effect of educational videos on preconception nutrition on knowledge and attitudes among premarital women - Komalasari Komalasari; Siska Ayunani; Yetty Dwi Fara; Inggit Primadevi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Women of reproductive age are a group that requires special attention regarding health and nutritional status during the preconception period, as nutritional conditions prior to pregnancy play a crucial role in determining maternal and infant health outcomes. Data from Pardasuka Health Center in 2024 recorded 487 pregnant women, of whom 79 (16.2%) experienced chronic energy deficiency (CED) and 37 (7.6%) had anemia. Furthermore, of the total 116 pregnant women with CED and anemia in 2024, 14 (12.1%) delivered low birth weight (LBW) infants and 14 (12.1%) delivered stunted infants. Nutritional interventions and preconception education delivered through digital media have been shown to be effective in improving knowledge and attitudes related to reproductive health and nutrition. Purpose: to determine the effect of educational videos on preconception nutrition on the knowledge and attitudes of premarital women. Method: The study employed a quasi-experimental design using a one-group pretest–posttest approach. The study population consisted of prospective brides, with a sample of 20 respondents selected through consecutive sampling. The statistical analysis used in this study was the McNemar test. Results: The results showed that educational videos on preconception nutrition had a significant effect on the knowledge of premarital women in the working area of the UPTD Pardasuka Health Center in 2025 (p-value = 0.031; p < 0.05). Conclusion: The educational videos also had a significant effect on the attitudes of premarital women in the same area (p-value = 0.008; p < 0.05). Suggestion: It is expected that premarital women utilize digital media to obtain continuous health education and adopt healthy behaviors from an early stage.